PELAKSANAAN STANDARD OPERATIONAL PROCEDURE (SOP) WAITER/WAITRESS ROOM SERVICE FOOD AND BEVERAGE DEPARTMENT PADA MASA PANDEMI COVID-19 DI FOX HOTEL PEKANBARU - Almas Refin; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Standard operational procedure (SOP) is the most important part in carrying out a task so that the task can be carried out properly and correctly. In the SOP room service, there are three stages, namely taking orders, operational activities, and clear-up. This study aims to find out how to implement the waiter/waitress room service SOP at Fox Hotel Pekanbaru, especially during the covid-19 pandemic. This study uses a qualitative method with a descriptive approach. Data collection techniques used in this study were observation, interviews, and documentation. Key informants involved in this research are Mr. Andi Alfian as manager at the food and beverage service department at Fox Hotel Pekanbaru and Mr. Samuel Simatupang as supervisor at the food and beverage service department at Fox Hotel Pekanbaru and an additional informant, namely Ms. Elsa Rianty as a waitress at the food and beverage service department at Fox Hotel Pekanbaru. Based on the results of the study, the implementation of SOP room service during the COVID-19 pandemic by waiters/waitresses at Fox Hotel Pekanbaru has gone well. Starting from taking orders, operational activities or food delivery, to clear-up or cleaning dirty dishes and food utensils. Of course there are obstacles in the implementation of SOP room service by the waiter/waitress themselves such as during rush hour, the waiter/waitress is overwhelmed in serving room service orders, but these obstacles can be overcome properly.  Keywords: Room Service, SOP, waiter, waitress, Covid-19